2021
DOI: 10.1371/journal.pone.0239168
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in COVID-19 mortality in Mexico: A cross-sectional study based on national data

Abstract: Introduction Across the world, the COVID-19 pandemic has disproportionately affected racial and ethnic minorities. How ethnicity affects Indigenous peoples in Mexico is unclear. The aim of this cross-sectional study was to determine the mortality associated with ethnicity, particularly of Indigenous peoples, in a large sample of patients with COVID-19 in Mexico. Methods We used open access data from the Mexican Ministry of Health, which includes data of all confirmed COVID-19 cases in the country. We used de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 21 publications
1
27
0
5
Order By: Relevance
“…Studies reported a disproportionately higher impact of COVID-19 among Indigenous populations from Mexico, Colombia, and among Mayan immigrants living in the USA when compared to their non-Indigenous counterparts [ 42 45 ]. Indigenous Ecuadorians experienced a 220% increase in the expected number of deaths during the pandemic, the highest level of excess deaths among all ethnic groups [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported a disproportionately higher impact of COVID-19 among Indigenous populations from Mexico, Colombia, and among Mayan immigrants living in the USA when compared to their non-Indigenous counterparts [ 42 45 ]. Indigenous Ecuadorians experienced a 220% increase in the expected number of deaths during the pandemic, the highest level of excess deaths among all ethnic groups [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, African Americans were more impacted because they have limited access to single-family homes due to historical institutional discriminatory policies (e.g., redlining and FHA policies) that force them to converge in mostly the poorest, densely populated inner-city spaces [78]. Similar experiences exist for Black, Asian, and Minority Ethnic (BAME) groups in the United Kingdom [34,[86][87][88][89] and indigenous populations around the world [90][91][92][93]. Generally, minorities are disproportionately overrepresented in neighborhoods of concentrated poverty [94], which is detrimental to mental and physical health and wellbeing.…”
Section: Structural Racismmentioning
confidence: 99%
“…• In Mexico, Indigenous people had higher odds of dying than non-Indigeneous people,with hospitalised Indigenous patients at 1.13 times higher risk of dying of COVID-19 than non-Indigenous patients (Ibarra-Nava et al, 2021 [75]).…”
Section: Ethnicitymentioning
confidence: 99%